2021
DOI: 10.1002/sdtp.14460
|View full text |Cite
|
Sign up to set email alerts
|

41.1: Invited Paper: [Invited] Textile‐OLEDs with high wearing comfort used for fashion displays and phototherapy applications

Abstract: Clothing‐type, textile‐based OLEDs and their bio‐medical application have been investigated. Textile‐based OLEDs have shown wide applicability and washability as well as high flexibility for a wearing textile displays. Furthermore, a novel phototherapy for neonatal jaundice by using textile‐OLEDs was proposed in this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Flexible displays not only are a core technology of mobile devices 1−5 but also used in many emerging fields, such as optical neurostimulation, 6 therapy, 7 and imaging. 8 Because of the high quantum yield and photochemical stability of quantum dots (QDs) than other semiconductor materials, 9−18 quantum-dot light-emitting diodes (QLEDs) are potentially used as key components for next-generation flexible displays.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flexible displays not only are a core technology of mobile devices 1−5 but also used in many emerging fields, such as optical neurostimulation, 6 therapy, 7 and imaging. 8 Because of the high quantum yield and photochemical stability of quantum dots (QDs) than other semiconductor materials, 9−18 quantum-dot light-emitting diodes (QLEDs) are potentially used as key components for next-generation flexible displays.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Flexible displays not only are a core technology of mobile devices but also used in many emerging fields, such as optical neurostimulation, therapy, and imaging . Because of the high quantum yield and photochemical stability of quantum dots (QDs) than other semiconductor materials, quantum-dot light-emitting diodes (QLEDs) are potentially used as key components for next-generation flexible displays. Some rigid QLEDs have been transformed into a flexible architecture with substrates, such as plastic, paper, and fabric. ,, For example, Kim et al reported an ultrathin flexible QLED consisting of indium tin oxide (ITO) anodes and lithium-doped aluminum (Li:Al)/gold cathodes .…”
Section: Introductionmentioning
confidence: 99%